Relationship of Chronic Energy Lack of Pregnant Women with LBW Incidence - Mardiyana, Rina (Kirana Publisher (KNPub), 2023)
LBW is the cause of infant death in East Java. This is influenced by KEK which causes babies to be born prematurely. The aim of this study was to determine the relationship between chronic energy deficiency in pregnant women and the incidence of LBW. The analytical research design uses a retrospective cohort using 53 samples calculated by the Slovin formula and total sampling in the technique. The data analysis used was univariate and bivariate chi-square. By getting the results from 16 respondents experiencing LBW as much as 30.2%, and as many as 20 pregnant women respondents experiencing CED 37.7%. Based on the analysis test, it was found that half of the pregnant women with CED had LBW as much as 50.0%. While the results of the bivariate analysis with chi-square obtained a p-value of 0.014 where p <α 0.05 which stated that there was a relationship between pregnant women with CED and the incidence of LBW in PMB Cemandi. The OR value is 4.5 which states that pregnant women with CED have a 4.5 times risk of having a baby with LBW.